Genetic determinants of warfarin maintenance dose and time in therapeutic treatment range: a RE-LY genomics substudy. (August 2016) - Eriksson, Niclas; Wallentin, Lars; Berglund, Lars; Axelsson, Tomas; Connolly, Stuart; Eikelboom, John; Ezekowitz, Michael; Oldgren, Jonas; Paré, Guillaume; Reilly, Paul; Siegbahn, Agneta; Syvanen, Ann-Christine; et al.
Aims: We investigated associations between genetic variation in candidate genes and on a genome-wide scale with warfarin maintenance dose, time in therapeutic range (TTR), and risk of major bleeding.Materials & methods: In total, 982 warfarin-treated patients from the RE-LY trial were studied.Results: After adjusting for SNPs in VKORC1 and CYP2C9, SNPs in DDHD1 (rs17126068) and NEDD4 (rs2288344) were associated with dose. Adding these SNPs and CYP4F2 (rs2108622) to a base model increased R 2 by 2.9%. An SNP in ASPH (rs4379440) was associated with TTR (-6.8% per minor allele). VKORC1 was associated with time less than INR 2.0. VKORC1 and CYP2C9 were associated with time more than INR 3.0, but not with major bleeding.Conclusions: We identified two novel genes associated with warfarin maintenance dose and one gene associated with TTR. These genes need to be replicated in an independent cohort.